Buttonhole: requirements and experience - Krystyna Charytoniuc (RDPLF, 2019)
Home hemodialysis requires total autonomy from the patient, who punctures himself. To this end, the vascular approach must be of good quality and the puncture technic should be easy to handle. A recognized approach is the "Buttonhole" technique. An easy technique, it encourages patients to continue their dialysis at home. But the risk of arterio-venous fistula (AVF) infection related to the puncture of the "Buttonhole" is very high. However, this technique has many positive points for the AVF itself, for the patients and for the caring teams. We looked for ways to improve this technique and eliminate as much as possible the risk of infection and to maintain the functionality of the fistula. We present our experience in this field.